1994
DOI: 10.1002/syn.890170104
|View full text |Cite
|
Sign up to set email alerts
|

The effects of chronic haloperidol administration on GABA‐immunoreactive. Axon terminals in rat medial prefrontal cortex

Abstract: Several reports have suggested that chronic haloperidol (HAL) treatment induces ultrastructural changes in synapses of substantia nigra, corpus striatum, and medial prefrontal cortex (mPFC) of rat brain. The effects of HAL on specific cortical transmitter systems, however, are not well characterized. Recent studies have indicated that there may be a loss of gamma-aminobutyric acid (GABA)ergic cells in anterior cingulate cortex of schizophrenic subjects and this hypothesis has prompted interest in the question … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 47 publications
5
26
0
1
Order By: Relevance
“…In an earlier study, GAD 65 -containing terminals showed APD dose-related increases, suggesting that these drugs may contribute to compensatory sprouting of GABAergic terminals, particularly in the SO of CA3/2 (18). Consistent with this, rats receiving chronic administrations of haloperidol showed marked increases in the number of GABAcontaining terminals forming axosomatic contacts with pyramidal neurons in the medial prefrontal cortex (19). Moreover, in the current report, mRNA for GAD 65 showed no significant changes in either SZs or BDs, suggesting that APD exposure might have increased its expression to normal levels.…”
Section: Discussionsupporting
confidence: 88%
“…In an earlier study, GAD 65 -containing terminals showed APD dose-related increases, suggesting that these drugs may contribute to compensatory sprouting of GABAergic terminals, particularly in the SO of CA3/2 (18). Consistent with this, rats receiving chronic administrations of haloperidol showed marked increases in the number of GABAcontaining terminals forming axosomatic contacts with pyramidal neurons in the medial prefrontal cortex (19). Moreover, in the current report, mRNA for GAD 65 showed no significant changes in either SZs or BDs, suggesting that APD exposure might have increased its expression to normal levels.…”
Section: Discussionsupporting
confidence: 88%
“…These data suggest that there may be an intrinsic reduction of GABAergic terminals in the hippocampus of schizophrenics and the therapeutic efficacy of the neuroleptic drugs may involve, at least in part, a trophic sprouting of these terminals. This conclusion is consistent with a controlled study in rat medial prefrontal cortex (anterior cingulate region) in which chronic haloperidol administration was associated with a marked increase of GABA-IR terminals (Vincent et al 1994b). …”
Section: Postmortem Evidence For a Gaba Defect In Schizophreniasupporting
confidence: 91%
“…This compound did not, however, alter striatal D, receptor number. Finally, it should be noted that while these findings support a role for 5-HT's ability to modulate striatal DA, the findings observed with PET may also result from 5-HT's ability to modulate other neurotransmitter systems (i.e., GABA, sigma opiates) that in turn modulate striatal DA release (Vincent et al, 1994). In fact, it is conceivable that the net effect of 5-HT on striatal DA modulation is via an inhibitory role on another neurotransmitter system that inhibits striatal DA release.…”
Section: Discussionmentioning
confidence: 79%